The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.devcel.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Rif1 Maintains Telomere Length Homeostasis of ESCs by Mediating Heterochromatin Silencing

Abstract: SUMMARY Telomere length homeostasis is essential for genomic stability and unlimited self-renewal of embryonic stem cells (ESCs). We show that telomere-associated protein Rif1 is required to maintain telomere length homeostasis by negatively regulating Zscan4 expression, a critical factor for telomere elongation by recombination. Depletion of Rif1 results in terminal hyperrecombination, telomere length heterogeneity, and chromosomal fusions. Reduction of Zscan4 by shRNA significantly rescues telomere recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 57 publications
15
117
0
Order By: Relevance
“…Interestingly, Rif1 is known to interact with Sirt3, Sirt7 (40), and Setdb1 (41,42). Sirt3 and Sirt7 deacetylate histones, whereas Setdb1 methylates histone at H3-K9.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Rif1 is known to interact with Sirt3, Sirt7 (40), and Setdb1 (41,42). Sirt3 and Sirt7 deacetylate histones, whereas Setdb1 methylates histone at H3-K9.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Zscan4 in ESCs is associated with rapid telomere extension by promoting T-SCE (Zalzman et al 2010;Dan et al 2014). Zscan4 is specifically expressed in 2Cs, and telomere elongation takes place most dramatically at the 2C stage through a T-SCE-based mechanism (Liu et al 2007).…”
Section: Role Of Tet Proteins In Repeat Silencing and Telomere Regulamentioning
confidence: 99%
“…One study claimed that NHEJ repair mechanism is observed very frequently in pancreatic cancer and another study showed that RIF1 gene increases the efficiency of NHEJ repair mechanism [3,4]. The next step to elucidate the role of RIF1 gene could be to use siRNA's to silence the gene as and then observe the effect in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…High expression levels of RIF1 are associated with transformation in ESC's [3]. RIF1 also promotes NHEJ in stem cells; thus, it avoids chemotherapy in cancer stem cells [4].…”
mentioning
confidence: 99%